Erratum to “Biology and the Statistic Demographic of Aphis glycines Matsumura (Hemiptera: Aphididae) on the Soybean with Plant Growth Promoting Rhizobacteria (PGPR) Treatment” [Jurnal Perlindungan Tanaman Indonesia, 24(1), 54‒60] - Jurnal Perlindungan Tanaman Indonesia (Jurnal Perlindungan Tanaman Indonesia, 2021)
This is a correction to: Biology and the Statistic Demographic of Aphis glycines Matsumura (Hemiptera: Aphididae) on the Soybean with Plant Growth Promoting Rhizobacteria (PGPR) Treatment. Jurnal Perlindungan Tanaman Indonesia, 24(1), 54‒60. https://doi.org/10.22146/jpti.49846 In Author’s affiliation, typed as:Hermanu Triwidodo1)*, Anggun Agustini1),  & Listihani1)1)Department of Plant Protection, Faculty of Agriculture, IPB UniversityJln. Kamper, Kampus IPB Dramaga, Bogor, West Java 16680 IndonesiaTherefore, the Author’s affiliation was corrected to:Hermanu Triwidodo1)*, Anggun Agustini1), & Listihani2)1)Department of Plant Protection, Faculty of Agriculture, IPB UniversityJln. Kamper, Kampus IPB Dramaga, Bogor, West Java 16680 Indonesia2)Faculty of Agriculture and Business, University of Mahasaraswati DenpasarJln. Kamboja No.11 A, Dangin Puri Kangin, Denpasar Utara, Bali 80233 Indonesia The editorial staff apologizes for the inconvenience. The online version of the corrected manuscript has been published in the open journal system of the Jurnal Perlindungan Tanaman Indonesia.